Toward a More Pro-Poor and Explicit Health Benefit Package in the Kyrgyz Republic : A Critical Review of the Stated Guaranteed Benefit Package and Options for Its Revision - World Bank (World Bank, Washington, DC, 2019)
The Kyrgyz Republic has made significant steps in reforming the health system through successive National Health Programs implemented over the last 20 years. One of the major achievements of such reforms were the establishment of a single-payer national health insurance and a basic benefit package. The State Guaranteed Benefit Package (SGBP) provides free basic health services at the primary care level for the whole population, and inpatient care with nominal co-payments or no fee for certain groups. Even though the principles of the SGBP contain elements of international good practice, the SGBP has hardly changed since it was stablished. At the same time, many changes have taken place within and outside the health system, exerting mounting pressure for the SGBP to adapt to the new disease burden and meet population’s expectations within the context of budget constraints. The current paper provides a critical assessment of the Kyrgyz Republic’s basic health benefit package. It reveals several issues in the actual benefits delivered to the population as opposed to the generous promise of the statutory package. Some important limitations include lack of clarity, persistent funding gap, large number of fee exemption categories given the resource constraints and at the same time lack of an effective mechanism to protect the poor. Most importantly, there is no systematic arrangement in place to ensure a regular evidence-based process of the benefit package revision. The paper proposes several measures that could guide the process of SGBP revision, considering the Kyrgyz context and building on international experiences. It is expected that information from the paper will be useful not only for the Kyrgyz stakeholders but also other countries in making the benefit package an effective instrument for achieving universal health coverage.